Beveridge Report Sub-committee : agreed statement of conclusions
1943-03-18 1943 1940s 4 pages The Beveridge Report contains details of twenty-three principal changes (Part 11), not all of them wholly satisfactory, in our opinion. In addition to the six key-points set out in the previous page, we strongly support the proposals to:- (a) abolish the system of Approved Societies; (b) provide marriage, maternity and funeral benefits; (c) equalise benefits for unemployment, disability and sickness; (d) transfer work from Local Authorities and abolish overlapping of Government Departments; (e) abolish exceptions from Insurance. We do not fully agree to the following proposals, and we have indicated briefly our reasons for Suggesting that they may need further consideration and possible amendment. 1. One stamp to cover all contributions may lead to a heavy financial loss where the card is accidentally destroyed. A comprehensive lump sum payment covering a number of employees (as for Income Tax) might be better. 2. Workmen's Compensation. We cannot agree to the proposed differentiation between the employers' contributions in hazardous and non-hazardous industries. A 'pooling of risks' should carry with it a pooling of responsibility to provide for risks throughout all industries. 3. We feel that Maternity Benefit, as proposed, is unfair to wives not gainfully employed. They get only the lump sum payment of £4: it should be possible to make some provision for them to be paid a weekly benefit for a period after childbirth, to enable them to hire assistance and domestic help during post-confinement weakness. 4. We cannot agree that a housewife widowed after many years of independence in her own home should be compelled to work, by withdrawal of benefit after a few weeks. The age of 60, fixed as the minimum pension ago, is, in the case of widows, unnecessarily harsh. Subject to adequate safeguards, this minimum age could be reduced to avoid forcing widows of fifty or over into industry, by the whip of poverty and destitution. We are now compelled to add a final word about the points in the Report with which we absolutely disagree in principle. They are not points which are necessary to the provision of a Charter of Social Security, and we would like to see them omitted. They are:- 1. The transition period of twenty years. This is open to many objections, such as (a) the impossibility of forecasting economic or social conditions for twenty years ahead; (b) the fact that full benefit is postponed for a long time and the means test retained to supplement an inadequate benefit; and (c) the element of doubt which it must raise in the minds of people whether full benefit will ever be paid. A fixed rate, revised every three years, according to cost of living, is suggested as a substitute. 2. Differentiation in rates of benefit between men and women should not be introduced into a forward-looking scheme. It is out of date and unjust. 292/150.5/5/62